Perilaku Pedagang Pengecer dalam Menghadapi Fluktuasi Harga Cabai Rawit di Pasar Badung - ANDIANI, JUNILLA; DEWI, RATNA KOMALA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.2, Desember 2024, 2024)
Retailer's Behavior in Facing Fluctuations of Cayenne Pepper Prices in Pasar Badung.  Price fluctuations are spikes or inaccuracies in anything that can be depicted on a graph. This research aims to describe the price fluctuations of cayenne pepper and analyze the behavior of retailers in dealing with price fluctuations of cayenne pepper at Badung Market based on three aspects, namely knowledge, attitudes and skills of traders. The location of the research was Badung Market, Denpasar City. The price of cayenne pepper decreased by 19.57% in May-June 2021, but the price of cayenne pepper increased drastically by 102.28% in May-June 2022. This shows that the price of cayenne pepper is difficult to predict and fluctuates greatly. The level of knowledge of retailers who use cayenne pepper as their main product is in the good category with an average score of 0.82. The level of knowledge of retailers who use cayenne pepper as a complementary product falls into the fair category with an average score of 0.62. As many as 80% of traders who use cayenne pepper as their main product strongly agree and another 20% disagree with the price fluctuations of cayenne pepper. As many as 75% of traders who use cayenne pepper as a complementary product strongly disagree and another 25% disagree with the price fluctuations of cayenne pepper. The difference in the skills of retailers who use cayenne pepper as the main product and retailers who use cayenne pepper as a complementary product lies in determining the amount of inventory when the demand and supply of cayenne pepper changes. Retail traders who have a low level of knowledge regarding price fluctuations in cayenne peppers must be more proactive in collecting price, demand and supply information and all cayenne pepper retailers must play a role in maintaining price stability.